2021
DOI: 10.1051/e3sconf/202126801030
|View full text |Cite
|
Sign up to set email alerts
|

Research on the effects of idling start-stop function on light vehicles fuel consumption and emission under different cycle conditions

Abstract: The idling distribution characteristics of NEDC, WLTC and CLTC conditions were analyzed, and the exhaust emissions and fuel consumption of three light gasoline vehicles when the idling start-stop function was turned on and off under different cycle conditions were measured. The effects of idling start-stop function on light vehicle fuel consumption and emissions under different cycle conditions were analyzed. The results show that the vehicle fuel saving rate of the idling start-stop function in three cycle co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Wang et al (2020b) found that fuel consumption between WLTC and RDE was at the same level, while the fuel consumption of CLTC-P was 8.41% higher than that of WLTC. Some studies (Geng et al 2021;Ma et al 2021;Yang et al 2021) also have investigated the emission characteristics of different emission control technology routes under the CLTC-P. However, there is still a lack of a large number of test research on CLTC-P, and a uni ed method for quantitatively evaluating CO 2 emissions measured under different test cycles is yet to be established.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al (2020b) found that fuel consumption between WLTC and RDE was at the same level, while the fuel consumption of CLTC-P was 8.41% higher than that of WLTC. Some studies (Geng et al 2021;Ma et al 2021;Yang et al 2021) also have investigated the emission characteristics of different emission control technology routes under the CLTC-P. However, there is still a lack of a large number of test research on CLTC-P, and a uni ed method for quantitatively evaluating CO 2 emissions measured under different test cycles is yet to be established.…”
Section: Introductionmentioning
confidence: 99%